Comunidades de prática à luz do regime de informação: ações de informação no Instituto Federal da Paraíba - Llarena, Marco Antonio Almeida (2022)
This study focused on the Instituto Federal de Educação, Ciência e Tecnologia da Paraíba, and proposes to the institution the promotion of group arrangements analogous to communities of practice as an informal resource to energize the informational flow in decision making and problem solving demanded by the formal activities and/or signaled om the information regime itself. It aimed to analyze, in the light of the information regime, the group arrangements analogous to the "communities of practice" at IFPB resulting from the actions of information in the management betweeen education, research and extension; to establish a conceptual and methodological approach between the ideas of communities of practice and information regime under the prism of Information Science; to configure the Information Regime of the Instituto Federal de Educação, Ciência e Tecnologia da Paraíba, via the design and description of its elements: contexts, information actions, social actors, devices and artifacts; map the group arrangements analogous to communities of practice based on records of information actions on teaching, research and extension of an institution; and, to propose, in light of the Information Regime of the studied institution, a model of communites of practice that considers its informal nature and contributes to the formal demands of the institution through actions of information of managers of the academic tripod. Its methodological processes were guided by qualitative research, utilizing bibliographical, documental, exploratory, and descriptive research, and a case study. All of this under the technniques of questionnaire application and content analysis. It resulted in ponderings about the multiple and abrangent views of the information regime and the community practice, establishing weaves and vicissitudes of the relationship between the terms. It configured the group arrangements of the selected institution through the records of information action that can energize the collaborative learning process mediated by information actions aimed at management activities in teaching, research and extension. The final product of the validated thesis was a model of a community of practice under the sustainable and dynamic perspective that believes it contemplates its informal nature in the institution and contributes in its formal demands through the information actions of managers of its academic tripod. It concluded that the functioning cycle of the model represents the beginnning of the community of practice in the selected institution, as well as in other institutions, and also that its growing can happen with the utilization of available information devices, qualifying the stages of development through the information actions that energize the sharing and integration of the group members via information artifacts. It also concludes that the good practices of the involved social actors can be facilitated and optimized, avoiding dispersion and/or enabling innovation via the re-signification of the contexts and domains intially considered. And, finally, it is believed that the proposal of the model can serve as guidance and/or a work tool at the institution in its multicampi structure.